A Systematic Approach to Reducing Compressor Downtime by 95.3% Within Six Months Toward Industry 4.0 Implementation - Rahmat; Yudha Witanto; Dimas Suryo Ajitomo; Budi Sunarto; Acim Maulana; Pedro da Silva (The Indonesian Institute of Science and Technology Research, 2026)
Workshop is one of the sections in the company that is tasked with supporting the productivity process, from Welding fabrication work, motor rewinding, machine tool work, to punch procurement (Mold). Supported by various machines used to support the production process, both for punch repair and fabrication. For this reason, the workshop always tries to provide the best, namely by creating improvements to speed up the process of procuring punches, both lower and upper, as well as master motifs and plain, while the improvements made are making improvements in the Compressor area. Thus, this compressor machine is a vital supporter of the machine's running process and product water usage services to achieve the target results of punch repair in the workshop, the purpose of the research is to add an automatic remote control at the nearest location & can be operated with Wi-Fi, create an auto evaporator cleaning program, install a compressor alarm notification, create an auto drain program for the compressor tube, create a safe compressor room. By implementing several improvements, the results were achieved by reducing downtime by 95.3% to 96.7%. Downtime decreased from 2784 minutes per 3 months to 92 minutes per 3 months. The potential profit was Rp 159.962.422 per year. Therefore, the research results can be applied to all workshop and production machines.